Typology of approaches to understanding the essence of trust property: Erbe der europäischen Wissenschaft: Wirtschaft, Management, Tourismus, Rechtsprechung [Heritage of European Science: Economics, Management, Tourism, Jurisprudence] Monografische Reihe «Europäische Wissenschaft» - Кіріяк; Kiriiak, Оксана; Oksana (My University, 2020)
The institution of trust property, which has a long history of development in foreign countries, for the national legal system is still in its infancy, due to a number of contradictions and difficulties associated with both scientific and theoretical justification, and the possibility o f implementing these provisions in practice. In connection with the improvement of legislative regulation of trust relations in many countries and the actual elimination of dualism in common law countries in our time there is a significant convergence of trust institutions and trust property (trust management), resulting in the property-legal nature of the trust binding legal elements are becoming more and more obvious. All this has an influential effect on the practice of borrowing these institutions from the continental legal system, in which the recently outlined institutions are becoming more widespread.